1986
DOI: 10.1042/bj2360821
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides obtained from a blood-group-Sd(a+) Tamm-Horsfall glycoprotein. An n.m.r. study

Abstract: Treatment of Tamm-Horsfall urinary glycoprotein with Bacteroides fragilis endo-,J-galactosidase over a range of enzyme concentrations, pH and temperature resulted in the release of a small but constant proportion of the terminal sugars, which indicates the presence in the glycoprotein of relatively few enzyme-susceptible -GIcNAc8l-3Gal,/l-4GlcNAc-units. Three oligosaccharides were isolated from the enzyme digest and characterized as Galfl6-4GlcNAcfll-3Gal (I), NeuAcz2-3Gal/J1-4 GlcNAcf6l-3Gal (II) and GalNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
7
22
0
Order By: Relevance
“…Previously, a Sd"-active pentasaccharide, released from T-H glycoprotein by endo-fl-galaclosidase. has been charactcrized (Donald et al, 1983;Donald and Feeney, 1986). Furthermore, studies on glycopeptide mixtures indicated that the Sd" determinant is present in triantennary and tetraantcnnary compounds (Williams et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, a Sd"-active pentasaccharide, released from T-H glycoprotein by endo-fl-galaclosidase. has been charactcrized (Donald et al, 1983;Donald and Feeney, 1986). Furthermore, studies on glycopeptide mixtures indicated that the Sd" determinant is present in triantennary and tetraantcnnary compounds (Williams et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…1979;Soh et al, 1980;Afonso et al, 1981;Donald et al, 1982Donald et al, , 1983Williams et al, 1984;Serafini-Cessi et al, 1984a, b;Donald and Feeney, 1986;Dall'Olio et al, 1988;Smagula et al, 1990). Tn the present study the N-linked carbohydrates were enzymically released from T-H glycoprotein of one male donor by PNGase-F, and fractionated into more than 150 fractions by a combination of three liquidchromatographic techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, GalNAc H1 is observed at δ 4.73Ϫ4.76 (42°C), while its NAc signal resonates at δ 2.015Ϫ2.019. Due to the attachment of GalNAc to Gal via a (β1-4) linkage, Gal H4 resonates at δ 4.11Ϫ4.12 and H3 at δ 4.15 (Williams et al, 1984;Donald and Feeney, 1986;Hård et al, 1992).…”
Section: Generalmentioning
confidence: 99%